Thermal properties of fired clay bricks from waste recycling. A review of studies - Ramos Gavilán, Ana Belén (2020)
The large waste volumes globally generated have increased environmental awareness, promoting recycling of waste as a sustainable construction material. This study presents a review of researches that analyse the thermal behavior of eco-friendly clay bricks that incorpore organic and mineral waste materials as an addition. Many of these works also provide data related to the composition of the material, and its physical, micro-structural and mechanical characteristics. Most of eco-friendly clay units increase the porosity of the ceramic, improving the energy efficiency of masonry enclosures, reducing the clay content and the energy consumption during the fire process. The positive effects of lightweight ceramics are an opportunity to improve the fire resistance inside green buildings.